Microvesicles Derived from Human Umbilical Cord Mesenchymal Stem Cells Enhance Alveolar Type II Cell Proliferation and Attenuate Lung Inflammation in a Rat Model of Bronchopulmonary Dysplasia - Ou Zhou; Jingyi You; Xiaochuan Xu; Jiang Liu; Huijun Qiu; Chang Hao; Wenjing Zou; Wenjie Wu; Zhou Fu; Daiyin Tian; Lin Zou (Stem Cells International)
Although it is known that exosomes derived from human umbilical cord mesenchymal stem cells (hUCMSCs) alleviate hyperoxic lung injury of bronchopulmonary dysplasia (BPD) in animal models, the role of microvesicles (MVs) derived from hUCMSCs in BPD is poorly defined. Furthermore, antenatal inflammation has been linked to high risk of BPD in preterm infants. The purpose of this study was to explore whether MVs derived from hUCMSCs can preserve lung structure and function in an antenatal lipopolysaccharide- (LPS-) induced BPD rat model and to clarify the underlying mechanism. We demonstrate that antenatal LPS induced alveolar simplification, altered lung function, and dysregulated pulmonary vasculature, which restored by hUCMSCs and MVs treatment. Furthermore, MVs were large vesicles with a diameter of 100-900 nanometers and mostly uptaken by alveolar epithelial type II cells (AT2) and macrophages. Compared with the LPS-exposed group, MVs restored the AT2 cell number and SP-C expression in vivo and promoted the proliferation of AT2 cells in vitro. MVs also restored the level of IL-6 and IL-10 in lung homogenate. Additionally, PTEN/AKT and MAPK pathways were associated with the protection of MVs. Taken together, this study suggests MVs derived from hUCMSCs improve lung architecture and function in an antenatal LPS-induced BPD rat model by promoting AT2 cell proliferation and attenuating lung inflammation; thus, MVs provide a promising therapeutic vehicle for BPD treatment.